2018
DOI: 10.1186/s12964-018-0246-x
|View full text |Cite
|
Sign up to set email alerts
|

CaGdt1 plays a compensatory role for the calcium pump CaPmr1 in the regulation of calcium signaling and cell wall integrity signaling in Candida albicans

Abstract: BackgroundSaccharomyces cerevisiae ScGdt1 and mammalian TMEM165 are two members of the UPF0016 membrane protein family that is likely to form a new group of Ca2+/H+ antiporter and/or a Mn2+ transporter in the Golgi apparatus. We have previously shown that Candida albicans CaGDT1 is a functional ortholog of ScGDT1 in the response of S. cerevisiae to calcium stress. However, how CaGdt1 together with the Golgi calcium pump CaPmr1 regulate calcium homeostasis and cell wall integrity in this fungal pathogen remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
1
23
1
Order By: Relevance
“…The PMC1 - lac Z reporter and PMR1 - lac Z reporter were described in our previous study [28]. The β-galactosidase activity was determined using the substrate ONPG as described [2931]. Data are mean ± SD from six independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The PMC1 - lac Z reporter and PMR1 - lac Z reporter were described in our previous study [28]. The β-galactosidase activity was determined using the substrate ONPG as described [2931]. Data are mean ± SD from six independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…To identify genes regulated by CaCrz1, the wild type SN148 and its isogenic CRISPR mutant for CaCRZ1 were grown to log-phase at 30°C before they were treated with 0.2 M CaCl 2 for 2 h. Total RNA samples were extracted Qiagen RNeasy minikit protocol, and RNA integrity was evaluated using an Agilent 2100 Bioanalyzer (Agilent Technologies, USA) as described [45]. RNA-seq libraries were constructed using Illumina's miSEQ RNA Sample Preparation Kit (Illumina Inc., USA).…”
Section: Rna Sequencing and Data Analysismentioning
confidence: 99%
“…In the yeast C. albicans , the comparison of the double deletion strain to each of the single deletions indicates that CaGdt1p and CaPmr1p also interact at the genetic level. Indeed, further deletion of CaGDT1 in a strain deleted for CaPMR1 increases (i) its sensitivity towards cell wall and ER stresses, (ii) its ability to accumulate radioactive 45 Ca 2+ , and (iii) its hypersensitivity to inhibitors of the Ca 2+ -mediated calcineurin signaling pathway [ 24 ]. Transcriptomic analyses further revealed that CaGdt1p is involved in the regulation of cellular transport of metal ions and amino acids [ 24 ].…”
Section: The Upf0016 Family and Cation Transportmentioning
confidence: 99%
“…Indeed, further deletion of CaGDT1 in a strain deleted for CaPMR1 increases (i) its sensitivity towards cell wall and ER stresses, (ii) its ability to accumulate radioactive 45 Ca 2+ , and (iii) its hypersensitivity to inhibitors of the Ca 2+ -mediated calcineurin signaling pathway [ 24 ]. Transcriptomic analyses further revealed that CaGdt1p is involved in the regulation of cellular transport of metal ions and amino acids [ 24 ]. In this pathogen, CaGdt1p also interacts at the genetic level with the high-affinity plasma membrane Ca 2+ channel CaCch1p/CaMid1p, again strengthening the role of CaGdt1p in Ca 2+ homeostasis.…”
Section: The Upf0016 Family and Cation Transportmentioning
confidence: 99%